Praññʻ sūʹ krāʺ mha praññ sūʹ vanʻ thamʻʺ tacʻ ūʺ - Manʻʺ Taṅʻ (Cā pe Bimānʻ thutʻ praññʻ sūʹ lakʻ cvai cā cañʻ, 1994)
Based on the author's experiences as a divisional commissioner, while in the civil service of Burma.